A The Relationship Between Air Temperature and Humidity and Fly Density at Ceger Market, South Tangerang, In 2024 - Syafitri, Dini; Irmayana, Shinta; Puspawati, Catur; Saputra, Atang (SANITAS: Jurnal Teknologi dan Seni Kesehatan, 2025)
Flies are of the order Diptera and are a type of insect or animal vector that carries diseases. The spread of flies is affected by temperature, humidity, wind speed, color and aroma. An environment with poor sanitation, wet and dirty places such as garbage cans is a breeding ground that flies love very much. The market is the right place to measure fly density, because there are various kinds of activities in it. The results of the research at Ceger Market show that the level of fly density in food product sales places is included in the high category. The temperature ranges from 26.5-34.8°C. Humidity ranges from 61-85%. Wind speeds are 0 m/d and 1.1 m/d. Meanwhile, sanitation facilities including garbage cans, TPS, drainage, and toilets in Ceger Market are still not eligible.